An Outbreak of Carbapenem-Resistant Klebsiella pneumoniae of K57 Capsular Serotype in an Emergency Intensive Care Unit of a Teaching Hospital in China - Shao, Chunhong; Jin, Yan; Wang, Wei; Jiang, Meijie; Zhao, Shuping (Frontiers in Public Health, 2021)
The emergence of carbapenem-resistant hypervirulent K. pneumoniae (CR-hvKP) strains has increased the threat posed by K. pneumoniae. Here, we described an outbreak of 32 CR-hvKP isolates from the emergency intensive care unit (EICU) of a teaching hospital in China. 32 CRKp isolates were collected from 6 patients and their surrounding environment in EICU. Antimicrobial susceptibility testing was performed using VITEK 2 compact system, E-test or the broth microdilution method. All isolates were serotyped, antimicrobial resistance genes and virulence-associated genes were screened using PCR. Multilocus sequence typing (MLST) and pulse-field gel electrophoresis (PFGE) were employed to characterize the genetic relationships among the CPKP isolates. The virulence capability of 11 CRKp isolates from 6 patients was evaluated through Galleria mellonella larva infection assay. PFGE showed that all 32 isolates belonged to one cluster, and MLST revealed that belonged to ST11. All isolates exhibited high resistance to β-lactam antibiotics, quinolones, and aminoglycosides. They were susceptible to ceftazidime/averbatan, tigecycline, and colistin. All 32 isolates harbored blaKPC-2, blaSHV-11, blaTEM-1, rmtB, and qnrD. The serotype of all 32 isolates was K57. All 32 isolates contained 6 virulence genes, namely, fimH, iucB, mrkD, rmpA, uge, and wabG. Infection assays demonstrated high mortality in the Galleria mellonella model. Following measures implemented by the hospital, the outbreak was controlled. The mortality rate was 50.0%. The epidemiology of CR-hvKP should be monitored closely to detect early indications of this emerging public health threat.